2014
DOI: 10.1590/1806-9282.60.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus in oral mucosa from human immunodeficiency virus positive patients

Abstract: Objective: the detection rate of Epstein-Barr virus (EBV) is higher in people living with human immunodeficiency virus (HIV). In an attempt to contribute to our epidemiological understanding of this coinfection and to investigate the activity of EBV in normal oral mucosa, we performed a cross-sectional study with HIV-positive patients. Methods: oral smears from 145 HIV-positive patients were collected between March 2010 and March 2011. Nested polymerase chain reaction (PCR) and reverse transcriptase-PCR (RT-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
2
11
0
2
Order By: Relevance
“…A lower CD4þ T-cell count was associated with HPV infection and EBV viral load; higher HIV viral load was associated with EBV infection, and younger age at HIV diagnosis was associated with KSHV viral load. These associations likely reflect immunosuppression with increased susceptibility to oral virus infection or replication, and are consistent with the higher prevalence rates of both HPV and EBV in HIV-infected individuals [Hille et al, 2002;Miller et al, 2006;Webster-Cyriaque et al, 2006;McLemore et al, 2010;Gillison et al, 2012;Santos et al, 2014]. Overall, CD4þ T-cell counts were relatively high, suggesting that even subtle perturbations in CD4þ T-cell count may affect HPV and EBV positivity.…”
Section: Discussionsupporting
confidence: 61%
“…A lower CD4þ T-cell count was associated with HPV infection and EBV viral load; higher HIV viral load was associated with EBV infection, and younger age at HIV diagnosis was associated with KSHV viral load. These associations likely reflect immunosuppression with increased susceptibility to oral virus infection or replication, and are consistent with the higher prevalence rates of both HPV and EBV in HIV-infected individuals [Hille et al, 2002;Miller et al, 2006;Webster-Cyriaque et al, 2006;McLemore et al, 2010;Gillison et al, 2012;Santos et al, 2014]. Overall, CD4þ T-cell counts were relatively high, suggesting that even subtle perturbations in CD4þ T-cell count may affect HPV and EBV positivity.…”
Section: Discussionsupporting
confidence: 61%
“…In comparison, infected healthy periodontal sites and gingivitis lesions typically harbor herpesviruses copy counts in the range of 1,000–20,000/ml . Herpesviruses are also prominent in periodontitis of various syndromes and in periodontal lesions , saliva and oral mucosa of HIV‐infected individuals. Cytomegalovirus and Epstein–Barr virus occurred with high frequency in both shallow and deep periodontal pockets of patients with type 2 diabetes , which may partly explain the elevated risk of diabetic patients to develop periodontitis.…”
Section: Disease Associationsmentioning
confidence: 99%
“…Moreover, detection of markers for EBV is useful to study the virus pathogenesis in the epithelial tissues. In a previous study we reported the presence of EBV DNA and RNA in a sampling of asymptomatic HIV positive subjects (Santos et al 2014). Here we searched for EBV markers in five individuals carrying symptomatic oral diseases.…”
Section: Short Communicationmentioning
confidence: 93%